An analysis of risk factors for mortality in patients with bloodstream infections caused by carbapenem-resistant Klebsiella pneumoniae - ZHU Qiuli; GENG Miaomiao; WEI Ju; SHEN Yun; HU Dan; CHEN Chunxia; CHEN Haiwei; SUN Zhe (Shanghai yufang yixue)
ObjectiveTo explore the clinical characteristics and risk factors for 30-day mortality in hospitalized patients with bloodstream infections (BSI) caused by carbapenem-resistant Klebsiella pneumoniae (CRKP).MethodsData were obtained retrospectively from the electronic medical records of inpatients at a tertiary A-grade hospital in Shanghai from January 2016 to December 2023. The collected variables included age, gender, department, surgical treatment, empirical antibiotic therapy, Pitt Bacteremia score (PBS), Charlson comorbidity index (CCI), INCREMENT-CPE score (ICS), length of hospital stay, the time from CRKP-BSI to discharge and, etc. The follow-up period ended upon discharge, with the follow-up outcomes defined as in-hospital mortality or discharge. The endpoint was defined as death within 30 days (including day 30) caused by CRKP-BSI or infection-related complications. Patients who survived within 30 days after CRKP-BSI were classified into the survival group, while those who died within 30 days were classified into the death group. Independent risk factors for 30-day mortality in patients with CRKP-BSI were analyzed using univariate and multivariate Cox regression analysis.ResultsA total of 71 hospitalized patients with CRKP-BSI, comprising 51 males and 20 females, with an average age of (65.12±18.25) years, were included during the study period. The M (P25, P75) of hospital stay were 37.00 (24.00, 56.00) days, and M (P25, P75) of the duration from CRKP-BSI to discharge or death were 18.00 (7.00, 35.00) days. There were 20 deaths (28.17%) in the death group and 51 survivors (71.83%) in the survival group. The results of multivariate Cox regression analysis showed that the ICS as an independent risk factor for 30-day mortality in CRKP-BSI patients (HR=1.379, 95%CI: 1.137‒1.671, P=0.001). Each 1-point increase in the ICS was associated with a 37.9% increase in the risk of mortality.ConclusionThe ICS is found to be a risk factor for 30-day mortality in patients with CRKP-BSI, which may facilitate the prediction for the risk of 30-day mortality and thereby support clinical decision-making for patients with CRKP-BSI.